2005
DOI: 10.1021/ja0509432
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Easy Access to Dendrimer-like Poly(ethylene oxide)s

Abstract: Dendrimer-like poly(ethylene oxide)s (PEOs) were synthesized by an iterative divergent approach combining anionic polymerization of ethylene oxide from multi-hydroxylated precursors and branching reactions of PEO chain ends. Partial deprotonation of the hydroxyls (< 30%) and use of dimethyl sulfoxide as solvent proved crucial for a "controlled/living" polymerization of ethylene oxide at room temperature. These sequences of reactions allowed us to prepare a dendrimer-like PEO up to the eighth generation with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
155
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(157 citation statements)
references
References 77 publications
2
155
0
Order By: Relevance
“…As can be seen in Figure 1, the ionization of the terminal hydroxyl groups in PTHF can be accomplished via addition of sodium hydride, however, the ionized hydroxyls in PTHF should be lower than 50% for preventing initiator precipitation from THF. It was found that as the exchange reaction between alcoholate active center and hydroxyl group is much faster than the initiation rate, which leads to simultaneous growth of polymer chains [38,39]; therefore, accurate feeding of NaH is not necessary and as a result, the synthesis process becomes much easier to operate. Using our synthetic approach, three triblock copolymers were prepared and their molecular weights and polydispersity indexes were listed in Table 1.…”
Section: Results and Discussion 31 Synthesis Of Triblock Copolymersmentioning
confidence: 99%
“…As can be seen in Figure 1, the ionization of the terminal hydroxyl groups in PTHF can be accomplished via addition of sodium hydride, however, the ionized hydroxyls in PTHF should be lower than 50% for preventing initiator precipitation from THF. It was found that as the exchange reaction between alcoholate active center and hydroxyl group is much faster than the initiation rate, which leads to simultaneous growth of polymer chains [38,39]; therefore, accurate feeding of NaH is not necessary and as a result, the synthesis process becomes much easier to operate. Using our synthetic approach, three triblock copolymers were prepared and their molecular weights and polydispersity indexes were listed in Table 1.…”
Section: Results and Discussion 31 Synthesis Of Triblock Copolymersmentioning
confidence: 99%
“…Star polymers with varying numbers of arms have been widely produced and studied [1][2][3][4][5][6][7][8] and branched polymers of increasing complexity and diverse structures have evolved. These include H-shaped polymers [9][10][11][12][13][14][15], comb-shaped polymers [16][17][18][19][20][21][22][23][24][25][26][27][28] and more recently dendritically branched polymers [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. Fundamental to all these studies is the ability of the synthetic polymer chemist to control structural homogeneity and produce branched ...…”
Section: Introductionmentioning
confidence: 99%
“…DB of all the HP structures is chosen to be equal to 0.5 which stands between perfect dendrimer and linear chain. 44,48 The number of terminal beads of each HP structure depends solely on its DB. 45 For each of the above mentioned HP structures bearing a lower value of WI ͑min͒, which corresponds to a rather compact interior, as well as structures of higher WI ͑max͒ closer to a more open starlike shape, were examined.…”
Section: Model Description and Simulation Detailsmentioning
confidence: 99%